Safety analysis in the NGAC model - Tan, Brian, author; Davies, Ewan S. D., author; Ray, Indrakshi, author; Abdelgawad, Mahmoud A., author; ACM, publisher (Colorado State University. Libraries, 2025)
We study the safety problem for the next-generation access control (NGAC) model. We show that under mild assumptions it is coNP-complete, and under further realistic assumptions we give an algorithm for the safety problem that significantly outperforms naive brute force search. We also show that real-world examples of mutually exclusive attributes lead to nearly worst-case behavior of our algorithm.
Keywords: access control; next-generation access control; safety problem; computational complexity